Non-Halal Products Cause Infidelity - Mospa Darma (Proceeding International Seminar of Islamic Studies, 2019)
Halal product is an inseparable factor from the life of Muslims and becomes a benchmark for the worship that will be done every day, where products related to the daily lives of Muslims whether consumed daily or once in a good in the form of food, drinks, medicines, clothing, both into the human body or attached to the body in the form of cleaning the body or as a deodorizer, body mask, hair oil or used as body accessories. Non-halal products will result in all one's deeds will be void and vain so as to cause the person to fall into the abyss of sin both intentionally or unintentionally, because something that is forbidden cannot be mixed with the sacred again purifying even under any conditions.